Synthesis of Composites with Microfibrillated Cellulose and Polylactic Acid - Huang, Chongxing; Yan, Mengmeng; Wang, Juan; Shen, Xiaoyan; Wang, Lei; Chen, Yin (Asian Journal of Chemistry, 2012)
In this paper, we reported the synthesis of the composite prepared with microfibrillated cellulose and polylactic acid. The effects of various processing methods, the raw material of microfibrillated cellulose, processing temperature and the content of microfibrillated cellulose and the properties of the composite materials were discussed. The internal features of composites were characterized by scanning electron microscopy. The results showed that melt extrusion technique is better than physical mixture. Composite made of eucalyptus microfibrillated cellulose had a maximum tensile strength compared with that microfibrillated cellulose of bamboo and bagasse microfibrillated cellulose r, but the microfibrillated cellulose of bagasse has the best compatibility with polylactic acid. With the increase of processing temperature, the tensile properties of composite material were improved apparently, but the change of elongation at break is not obvious. With the addition of microfibrillated cellulose increased, the properties of composites decreased, when the content of microfibrillated cellulose was less than 20 %.